ESG Trend - The History of ESG Concept Formation and the Current Trends in the Goal of Business Sustainable Development - Thi Thu Thao, Thieu (VNU Journal of Science: Policy and Management Studies; Vol 39 No 2DO - 10.25073/2588-1116/vnupam.4385, 2023)
Faced with the great impact of the Covid-19 pandemic on the global economy, the ESG model with the combination of three factors Environment - Society - Governance (ESG) emerges as a typical ecosystem in the goal towards business sustainable development. ESG is considered as the basis for establishing national and global sustainable development goals.Aside from the perspective of financial investment safety, in this study, the author wishes to examine ESG from the standpoint of science and technology policy. The goal is to examine the history of the concept of ESG in relation to science and technology policy, as well as to explain why significant enterprises and technology companies throughout the world are focusing on adopting the ESG model to develop their businesses in the future.